The development of a Massive Open Online Course (MOOC) in mastering smoking cessation intervention in dentistry - Nurul Asyikin Yahya; Haslina Rani; Liew, Amy Kia Cheen; Ho, Ting Khee (Penerbit Universiti Kebangsaan Malaysia, 2019)
Purpose – Massive Open Online Courses (MOOC) has appeared as one of the most explored trends of online learning. In September 2014, the Ministry of Education Malaysia has collaborated with four of its public universities; including The National University of Malaysia (UKM) to launch the Malaysia MOOCs initiative. As part of this collaboration effort, our faculty developed a MOOC for Smoking Cessation Intervention in Dental Practice course for our faculty teaching and learning. Methodology – This course was developed using Iterative ADDIE (Analyse, Design, Develop, Implement and Evaluate) Instructional Design Framework. The smoking cessation intervention content of this course was adapted from the Smoking Cessation Intervention Delivered by Dentists (SCIDD) Training Module and UKM’s Oral Health Curriculum. The analytics data was collected from the MOOC via OpenLearning.com’s analytics tool and analysed in SPSS version 23. Findings – Eight modules were developed for this course. The learning content of each module contained a video, a power point lecture slides and quizzes in English language. The structure of learning tasks was loosely structured and learner controlled. A total of 224 learners enrolled for the course. Mostly were dental undergraduates (n=72, 33.6%). Sixty-three percent of the enrolled learners completed the course. Significantly more dental auxiliaries (p<0.000) completed the course compared to other types of learners. MOOC could be an alternative online learning platform for the topic of smoking cessation in the dental practices for all learners. Significance – MOOC would be an alternative platform for curricular teaching among students and lifelong learning for employment and personal fulfilment for health professionals or those with special interest in tobacco control.